Rehabilitating the Brownfield Zones of Budapest - Barta, Györgyi; Beluszky, Pál; Czirfusz, Márton; Győri, Róbert; Kukely, György (Discussion Papers, 2012)
The present volume was complied as the final study of the multiannual research of the Regional Research Centre of the Hungarian Academy of Sciences on the problem of brownfields in Budapest. The 22 authors of the volume investigated different aspects of the problems of the brownfields. The studies were prepared around four specific subjects, which present the current status of the rehabilitation of brownfields in Budapest. The structure of the volume is as follows: 1 The history of the industry in Budapest, the changes in the expansion of the former industrial zone. 2 The current status of the former industrial zone 3 Spontaneous renewal in the brownfield of Budapest 4 The brownfield rehabilitation plans of regional development and spatial plan¬ning.